To PLEX or Not to PLEX for Amiodarone-Induced Thyrotoxicosis - Tania Ahuja; Olivia Nuti; Cameron Kemal; Darren Kang; Eugene Yuriditsky; James M. Horowitz; Raymond A. Pashun (Case Reports in Cardiology)
Amiodarone-induced thyrotoxicosis (AIT) carries significant cardiovascular morbidity. There are two types of AIT with treatment including antithyroid medications and corticosteroids and treatment of ventricular arrhythmias. Therapeutic plasma exchange (TPE) also known as “PLEX” may help remove thyroid hormones and amiodarone. We report a case of PLEX in an attempt to treat cardiogenic shock secondary to AIT. This case highlights the robust rapidly deleterious demise of AIT, specifically in patients with decompensated heart failure. The decision to PLEX or not to PLEX for AIT should be individualized, prior to definitive therapy.